A corrosion-resistant composite material motor housing
Through the combination of polycarbonate, fluorine-containing silicone polycarbonate and inorganic materials, the mechanical, corrosion-resistant and flame-retardant properties of the motor shell are improved, and the weather resistance and cost-weight problems of traditional motor shells in humid environments are solved, thus achieving the problem of insufficient weather resistance and cost-weight of traditional motor shells in humid environments. The motor case is lightweight and low-cost.
Patent Information
- Application Number
- CN202311804095.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-26
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-12-26
AI Technical Summary
When used in humid and open-air environments, the weather resistance performance is insufficient, and the traditional metal shell increases the cost and weight of the motor. Non-metallic materials have defects in mechanical strength and corrosion resistance, especially the flame retardant performance needs to be improved. .
The raw materials such as polycarbonate, fluorine-containing silicone polycarbonate, inorganic materials and maleic anhydride grafted ethylene-octene copolymer are used to improve the phase interface morphology and dispersion, and combine silane coupling agent to treat the inorganic materials to form good Mechanical, corrosion-resistant, moisture-resistant and flame-retardant composite materials.
It realizes the lightweight and low cost of the motor case, improves mechanical properties, moisture and heat resistance and flame retardant properties, and can effectively replace metal materials and be suitable for humid environments.
Smart Images

Figure BDA0004629729640000121
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer technology, and in particular to a corrosion-resistant composite material motor casing. Background Art
[0002] The motor is composed of a stator and a rotor. The high-speed rotation of the rotor can drive the motor shaft to rotate at high speed. The motor shaft of the motor is connected to the transmission mechanism, so that the motor serves as the power source of the transmission mechanism. The motor is a device used to convert electrical energy into mechanical energy. The motor casing provides positioning support for the motor, protects the rotor and electronic coil inside the motor, and dissipates heat for the motor during operation.
[0003] When the existing motor casing is used for a long time in a humid, open-air environment, such as the hot and humid areas in the south and the extremely cold areas in the north, higher requirements are placed on the weather resistance of the motor casing material.
[0004] Most of the existing metal motor housings are made of metal materials, but this increases the cost and weight of the motor. The thinning and multifunctionalization of electronic and electrical equipment has become a research trend; non-metallic materials are often used to replace metal materials. Although non-metallic materials are not as good as metal materials in terms of mechanical strength, they have outstanding thermal conductivity and corrosion resistance. At the same time, non-metallic materials can be directly injection molded, with high product design freedom and lower production costs.
[0005] CN109022974A discloses a method for manufacturing a magnesium alloy motor housing and a motor housing, belonging to the field of automobile technology. The motor housing is made of magnesium alloy, and the manufacturing method includes the following steps: (1) smelting; (2) preheating the mold for making the motor housing to obtain the preheated mold; (3) pouring and solidification; (4) solution treatment: the solidified magnesium alloy is subjected to solution treatment to obtain the magnesium alloy after solution treatment; (5) quenching treatment: the magnesium alloy after solution treatment is subjected to quenching treatment, and then cooled to room temperature to obtain the magnesium alloy after quenching treatment; (6) cryogenic treatment: the magnesium alloy after quenching treatment is placed in liquid nitrogen for cryogenic treatment to obtain a magnesium alloy casting; (7) processing and forming. The motor housing has the above-mentioned method for manufacturing a magnesium alloy motor housing, and has the characteristics of strong plasticity and high strength.
[0006] CN110358294A discloses a high-strength heat-conducting nylon composite material and its preparation method and application, belonging to the field of polymer composite materials, the heat-conducting nylon composite material includes nylon resin: 100 parts; reinforcing material: 50-100 parts; heat-conducting material: 0.5-2.0 parts; flow modifier: 5-20 parts; dispersant: 0.3-0.8 parts; lubricant: 0.1-0.6 parts; antioxidant: 0.1-0.8 parts; coupling agent: 0.2-0.6 parts; the preparation method includes: surface treatment of heat-conducting material; preparation of mixing aids; preparation of heat-conducting flow masterbatch; preparation of high-strength heat-conducting nylon composite material; the heat-conducting nylon composite material is applied to medium-sized, small and micro motor housings, solving the problem of low strength and poor thermal conductivity of polymer composite materials. Compared with traditional metal housings, the motor housing of the present invention has the advantages of light weight, easy molding, corrosion resistance and weather resistance. However, the corrosion resistance and flame retardant properties need to be further improved. Summary of the invention
[0007] To achieve the above-mentioned purpose, the present invention provides a corrosion-resistant composite material motor casing, characterized in that it comprises the following raw materials: polycarbonate, polybutylene terephthalate, inorganic material, maleic anhydride grafted ethylene-octene copolymer (MAH-g-POE), antioxidant, and pentaerythritol stearate.
[0008] Further, a corrosion-resistant composite material motor housing comprises the following raw materials: 60-100 parts by weight of polycarbonate, 1-6 parts by weight of polybutylene terephthalate, 1-10 parts by weight of inorganic material, 1-10 parts by weight of maleic anhydride grafted ethylene-octene copolymer (MAH-g-POE), 1-5 parts by weight of antioxidant, and 1-5 parts by weight of pentaerythritol stearate;
[0009] The inorganic material is at least one of glass fiber, aluminum nitride, boron nitride, graphene, and carbon nanotubes.
[0010] Maleic anhydride grafted ethylene-octene copolymer (MAH-g-POE) can improve the interface morphology of polycarbonate and polybutylene terephthalate, improve the microstructure of the phase region, and achieve the purpose of physical compatibility.
[0011] Polycarbonate has excellent impact resistance, light transmittance, weather resistance and other properties, and is widely used in the automotive, aerospace, electrical appliances, medical and health fields; but it also has disadvantages such as easy cracking and poor impact toughness, and the ester group on its main chain is prone to hydrolysis in a hot and humid environment, resulting in a decrease in its overall performance; its own flame retardant properties are poor and other problems.
[0012] Further, a corrosion-resistant composite material motor housing includes the following raw materials: 60-70 parts by weight of polycarbonate, 10-30 parts by weight of fluorine-containing silicon polycarbonate, 1-6 parts by weight of polybutylene terephthalate, 1-10 parts by weight of inorganic material, 1-10 parts by weight of maleic anhydride grafted ethylene-octene copolymer (MAH-g-POE), 1-5 parts by weight of antioxidant, and 1-5 parts by weight of pentaerythritol stearate;
[0013] The preparation method of the fluorine-containing silicon polycarbonate comprises the following steps:
[0014] S1. Under a nitrogen atmosphere, 3-6 parts by weight of a silane compound is added to 50-80 parts by weight of a 50-60wt% ethanol aqueous solution and mixed evenly, the pH is adjusted to 5-5.8, and the mixture is heated to 60-70°C for 1-5 hours. After the reaction is completed, the mixture is centrifuged, washed, and dried to obtain a functionalized polysiloxane;
[0015] S2: 1-3 parts by weight of perfluorocyclohexyl methyl acrylate is added to 2-6 parts by weight of dioxane and mixed evenly, heated to 75-85°C, 0.01-0.1 parts by weight of thioglycolic acid and 0.01-0.05 parts by weight of initiator are added, and the mixture is continued for 3-6 hours, and the solvent is removed by distillation under reduced pressure to obtain a terminal carboxyl perfluoro polymer; 3-5 parts by weight of the terminal carboxyl perfluoro polymer and 0.1-0.5 parts by weight of pyridine are mixed evenly, and then 0.1-3 parts by weight of thionyl chloride are added, and the mixture is heated to 60-70°C for 1-5 hours, and then unreacted substances are removed by distillation under pressure, and then 0.05-0.4 parts by weight of mercaptoethanol and 0.05-0.6 parts by weight of triethylamine are added at 35-38°C, and the mixture is heated to 60-65°C for 1-5 hours. After the reaction is completed, the mixture is washed and distilled under reduced pressure to obtain a terminal mercapto perfluoro polymer;
[0016] S3: adding 1-2 parts by weight of polycarbonate diol and 0.1-0.5 parts by weight of 1,1,3,3-tetramethylguanidine to 30-80 parts by weight of N,N-dimethylacetamide and mixing them evenly; introducing CO2 at 1.0-1.3MPa and 28-30°C for 60-120min; adding 0.1-0.7 parts by weight of a halogen-containing double bond compound; continuing the reaction for 24-40h; after the reaction is completed, cooling to room temperature, filtering, washing, and drying to obtain a modified polycarbonate;
[0017] S4: adding 0.1-1 parts by weight of functionalized polysiloxane, 0.1-1 parts by weight of perfluoropolymer, 0.5-4 parts by weight of modified polycarbonate and 0.01-0.1 parts by weight of photoinitiator into 50-100 parts by weight of dichloromethane, mixing the mixture evenly, and irradiating the mixture under ultraviolet light to obtain fluorine-containing silicon polycarbonate.
[0018] Furthermore, the silane compound is a mixture of mercaptosilane, hydroxysilane and epoxysilane; the mercaptosiloxane is at least one of 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane and 3-mercaptopropylmethyldiethoxysilane. The hydroxysilane is trimethylhydroxysilane; the epoxysilane is γ-(2,3-epoxypropoxy)propyltrimethoxysilane;
[0019] Furthermore, the halogen-containing double bond compound is at least one of 3-chloro-2-methylpropene and allyl chloride.
[0020] Furthermore, the ultraviolet light irradiation condition is irradiation under a 300-500W ultraviolet lamp for 10-120 minutes.
[0021] Based on the above defects, the present application introduces fluorinated silicon polycarbonate, which interacts with polycarbonate, and can effectively retain and maintain the properties of polycarbonate, while synergistically improving its defects. In the present application, mercaptosilane, hydroxysilane, and epoxysilane are used as raw materials to prepare mercapto-containing polysiloxane; fluorine-containing compounds and thioglycolic acid are used as raw materials to prepare terminal carboxyl perfluoropolymers under the action of initiators; at the same time, terminal carboxyl perfluoropolymers and thionyl chloride are used as raw materials to prepare terminal mercapto perfluoropolymers; polycarbonate diol is used as raw material to prepare modified polycarbonate; mercapto-containing polysiloxane, terminal mercapto perfluoropolymer, and modified polycarbonate are used as raw materials, and mercapto-ene click chemistry reaction occurs under the action of ultraviolet light and photoinitiators to obtain fluorinated silicon polycarbonate. Fluorine-containing silicon polycarbonate has a three-dimensional network structure and interacts with polycarbonate to improve its resistance to moisture and heat aging, solvent resistance, and its corresponding mechanical properties. The introduction of polysiloxane improves the flame retardant properties of polycarbonate and expands the application field of polycarbonate materials.
[0022] Adding inorganic materials is a common method to improve the corrosion resistance of polycarbonate plastics. However, inorganic materials have poor compatibility with resins, which is not conducive to the dispersion of inorganic materials, thereby affecting its mechanical, solvent resistance, moisture and heat resistance, flame retardancy and other properties.
[0023] The inorganic material may also be an inorganic material modified by a silane coupling agent; the silane coupling agent is at least one of 3-isocyanate propyl trimethoxy silane and γ-(2,3-epoxypropoxy)propyl trimethoxy silane.
[0024] The preparation method of the silane coupling agent modified inorganic material comprises the following steps: adding the inorganic material and the silane coupling agent into an ethanol aqueous solution, mixing them evenly, ultrasonically treating them for 10-30 minutes, and then heating them to 70-90° C. to react for 1-5 hours. After the reaction is completed, centrifuging the precipitate, washing it, and drying it to obtain the silane coupling agent modified inorganic material.
[0025] The inorganic material is treated with a silane coupling agent to improve its dispersibility in polycarbonate, enhance the compatibility between molecules, and inhibit the migration of inorganic materials in polycarbonate composite materials, thereby improving its mechanical properties, moisture and heat aging resistance, and solvent resistance. At the same time, boron nitride nanosheets and carbon nanotubes have flame retardant properties. The silane coupling agent interacts with the inorganic material and the polysiloxane in the fluorine-containing silicon polycarbonate. The evenly dispersed carbon nanotubes and boron nitride nanosheets form a continuous and dense carbon layer during the combustion process, which increases the carbonization rate of the acrylic resin material and avoids the penetration of oxygen and heat into the material, thereby inhibiting the combustion process and improving the flame retardant properties.
[0026] The invention also provides a method for preparing a corrosion-resistant composite material motor casing.
[0027] A method for preparing a corrosion-resistant composite material motor casing comprises the following steps: uniformly mixing polycarbonate, fluorinated silicon polycarbonate, polybutylene terephthalate, inorganic material, maleic anhydride grafted ethylene-octene copolymer (MAH-g-POE), antioxidant and pentaerythritol stearate, and then adding the mixture into a twin-screw extruder, wherein the screw diameter of the twin-screw extruder is 30 mm, the screw speed is 110 r / min, the aspect ratio is 25, and the extruder is heated in 6 sections, wherein the temperature of each section from a feed port to a die is 180-185° C., 200-210° C., 230-235° C., 240-250° C., 230-235° C. and 220-225° C., and the mixture is granulated and added into an injection molding machine for injection molding to obtain a corrosion-resistant composite material motor casing.
[0028] The injection molding machine for injection molding in the present invention is not particularly limited.
[0029] Beneficial effects of the present invention:
[0030] 1. Compared with the prior art, the present application uses polycarbonate, fluorinated silicon polycarbonate, polybutylene terephthalate, inorganic materials, maleic anhydride grafted ethylene-octene copolymer (MAH-g-POE), antioxidants, and pentaerythritol stearate as raw materials. The raw materials interact with each other and have good mechanical, corrosion resistance, moisture and heat resistance, and flame retardant properties. The preparation method is simple and the cost is low. The corrosion-resistant composite material motor casing prepared by the present application can replace the metal material casing to achieve lightweight and low-cost motor casing.
[0031] 2. The present application introduces fluorinated silicon polycarbonate, which interacts with polycarbonate, effectively retains and maintains the properties of polycarbonate, and synergistically improves its defects. In the present application, mercaptosilane, hydroxysilane, and epoxysilane are used as raw materials to prepare mercapto-containing polysiloxane; fluorine-containing compounds and thioglycolic acid are used as raw materials to prepare terminal carboxyl perfluoropolymers under the action of initiators; terminal carboxyl perfluoropolymers and thionyl chloride are used as raw materials to prepare terminal mercapto perfluoropolymers; polycarbonate diol is used as raw material to prepare modified polycarbonate; mercapto-containing polysiloxane, terminal mercapto perfluoropolymer, and modified polycarbonate are used as raw materials, and mercapto-ene click chemistry reaction occurs under the action of ultraviolet light and photoinitiators to obtain fluorinated silicon polycarbonate. Fluorinated silicon polycarbonate has a three-dimensional network structure, which interacts with polycarbonate to improve its resistance to wet heat aging, solvent resistance, and its corresponding mechanical properties, and the introduction of polysiloxane improves the flame retardant properties of polycarbonate, expanding the application field of polycarbonate materials. DETAILED DESCRIPTION
[0032] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0033] Introduction of some raw materials used in the embodiments of the present invention:
[0034] Polycarbonate, brand A1220, Wanhua Chemical.
[0035] Polybutylene terephthalate, brand B2300G6HR, was purchased from Dongguan Huayun Plastic Raw Materials Co., Ltd.
[0036] Maleic anhydride grafted ethylene-octene copolymer (MAH-g-POE), brand SC0NA6402, BYK.
[0037] Boron nitride nanosheets, model NS-BN, were purchased from Suzhou Napu Material Technology Co., Ltd.
[0038] Carbon nanotubes: Multi-walled carbon nanotubes, diameter 40-60nm, length 1.25μm, sourced from Shenzhen Nanoport Co., Ltd.
[0039] Polycarbonate diol, product number HC0458, was purchased from Tianmen Hengchang Chemical Co., Ltd.
[0040] Other raw materials not mentioned are common raw materials in the art. The above content is only to help illustrate the present invention and should not be construed as a strict limitation of the present invention. Those skilled in the art can directly purchase or prepare the same / similar raw materials from the market. These contents will not be repeated in the examples.
[0041] The following will be combined with the specific embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] Example 1
[0043] A corrosion-resistant composite material motor housing comprises 100 parts by weight of polycarbonate, 4 parts by weight of polybutylene terephthalate, 8 parts by weight of inorganic material, 10 parts by weight of maleic anhydride grafted ethylene-octene copolymer (MAH-g-POE), 3 parts by weight of antioxidant 1010, and 3 parts by weight of pentaerythritol stearate;
[0044] The inorganic material is formed by mixing boron nitride nanosheets and carbon nanotubes in a mass ratio of 1:1.
[0045] A method for preparing a corrosion-resistant composite material motor casing comprises the following steps: according to a formula, polycarbonate, polybutylene terephthalate, inorganic material, maleic anhydride grafted ethylene-octene copolymer (MAH-g-POE), antioxidant 1010 and pentaerythritol stearate are uniformly mixed, and then added into a twin-screw extruder, wherein the screw diameter of the twin-screw extruder is 30 mm, the screw speed is 110 r / min, the aspect ratio is 25, 6-stage heating is performed, and the temperatures of each section from a feed port to a die are 185° C., 210° C., 235° C., 250° C., 235° C. and 225° C., granulation is performed, and the mixture is added into an injection molding machine for injection molding to obtain a corrosion-resistant composite material motor casing.
[0046] Example 2
[0047] A corrosion-resistant composite material motor housing, comprising 70 parts by weight of polycarbonate, 30 parts by weight of fluorine-containing silicon polycarbonate, 4 parts by weight of polybutylene terephthalate, 8 parts by weight of inorganic material, 10 parts by weight of maleic anhydride grafted ethylene-octene copolymer (MAH-g-POE), 3 parts by weight of antioxidant 1010, and 3 parts by weight of pentaerythritol stearate;
[0048] The inorganic material is formed by mixing boron nitride nanosheets and carbon nanotubes in a mass ratio of 1:1;
[0049] The preparation method of the fluorine-containing silicon polycarbonate comprises the following steps:
[0050] S1. Under a nitrogen atmosphere, 3 parts by weight of a silane compound is added to 50 parts by weight of a 50 wt% ethanol aqueous solution and mixed evenly, the pH is adjusted to 5.8, and the mixture is heated to 60° C. for 4 hours. After the reaction is completed, the mixture is centrifuged, washed, and dried to obtain a functionalized polysiloxane; wherein the silane compound is prepared by mixing 3-mercaptopropyltrimethoxysilane, trimethylhydroxysilane, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane in a mass ratio of 2:1:1;
[0051] S2: 3 parts by weight of perfluorocyclohexyl methyl acrylate is added to 6 parts by weight of dioxane and mixed evenly, heated to 84°C, 0.1 parts by weight of thioglycolic acid and 0.04 parts by weight of dibenzoyl peroxide are added, and the mixture is continued for 6 hours, and the solvent is removed by reduced pressure distillation to obtain a terminal carboxyl perfluoro polymer; 5 parts by weight of the terminal carboxyl perfluoro polymer and 0.5 parts by weight of pyridine are mixed evenly, and then 3 parts by weight of thionyl chloride are added, and the mixture is heated to 70°C for 4 hours, and then unreacted substances are removed by pressure distillation, and then 0.4 parts by weight of mercaptoethanol and 0.6 parts by weight of triethylamine are added at 38°C, and the mixture is heated to 62°C for 5 hours. After the reaction is completed, the mixture is washed and distilled under reduced pressure to obtain a terminal mercapto perfluoro polymer;
[0052] S3: 2 parts by weight of polycarbonate diol and 0.5 parts by weight of 1,1,3,3-tetramethylguanidine are added to 50 parts by weight of N,N-dimethylacetamide and mixed evenly; CO2 is introduced at 1.3 MPa and 30°C for 60 minutes; 0.7 parts by weight of allyl chloride is added and the reaction is continued for 40 hours; after the reaction is completed, the mixture is cooled to room temperature, filtered, washed and dried to obtain a modified polycarbonate;
[0053] S4: 1 part by weight of functionalized polysiloxane, 1 part by weight of terminal mercapto perfluoropolymer, 4 parts by weight of modified polycarbonate, and 0.1 parts by weight of photoinitiator (2,2-dimethoxy-2-phenylacetophenone) are added to 100 parts by weight of dichloromethane, mixed evenly, and irradiated under 300 W ultraviolet light for 60 minutes to obtain fluorine-containing silicon polycarbonate.
[0054] A method for preparing a corrosion-resistant composite material motor casing comprises the following steps: according to a formula, polycarbonate, fluorinated silicon polycarbonate, polybutylene terephthalate, inorganic material, maleic anhydride grafted ethylene-octene copolymer (MAH-g-POE), antioxidant 1010 and pentaerythritol stearate are uniformly mixed, and then added into a twin-screw extruder, wherein the screw diameter of the twin-screw extruder is 30 mm, the screw speed is 110 r / min, the aspect ratio is 25, 6-stage heating is performed, and the temperatures of each section from a feed port to a die are 185° C., 210° C., 235° C., 250° C., 235° C. and 225° C., granulation is performed, and the mixture is added into an injection molding machine for injection molding to obtain a corrosion-resistant composite material motor casing.
[0055] Example 3
[0056] A corrosion-resistant composite material motor housing, which is substantially the same as that of Example 2, except that the inorganic material is a silane coupling agent-modified inorganic material;
[0057] The preparation method of the silane coupling agent modified inorganic material is as follows: adding an inorganic material and a silane coupling agent to a 50wt% ethanol aqueous solution, mixing them evenly, ultrasonically treating them for 30 minutes, and then heating them to 80°C for reaction for 3 hours. After the reaction is completed, centrifuging and collecting a precipitate, washing, and drying to obtain the silane coupling agent modified inorganic material; wherein the mass ratio of the inorganic material, the silane coupling agent, and the ethanol aqueous solution is 1:0.5:15; wherein the inorganic material is formed by mixing boron nitride nanosheets and carbon nanotubes in a mass ratio of 1:1; wherein the silane coupling agent is formed by mixing 3-isocyanate propyltrimethoxysilane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane in a mass ratio of 1:2.
[0058] Example 4
[0059] A corrosion-resistant composite material motor housing, which is substantially the same as that of Example 2, except that: the fluorine-containing silicon polycarbonate is replaced by fluorine-containing polycarbonate;
[0060] The preparation method of the fluorinated polycarbonate comprises the following steps:
[0061] S1: 3 parts by weight of perfluorocyclohexyl methyl acrylate is added to 6 parts by weight of dioxane and mixed evenly, heated to 84°C, 0.1 parts by weight of thioglycolic acid and 0.04 parts by weight of dibenzoyl peroxide are added, and the mixture is continued for 6 hours, and the solvent is removed by distillation under reduced pressure to obtain a terminal carboxyl perfluoro polymer; 5 parts by weight of the terminal carboxyl perfluoro polymer and 0.5 parts by weight of pyridine are mixed evenly, and then 3 parts by weight of thionyl chloride are added, and the mixture is heated to 70°C for 4 hours, and then unreacted substances are removed by distillation under pressure, and then 0.4 parts by weight of mercaptoethanol and 0.6 parts by weight of triethylamine are added at 38°C, and the mixture is heated to 62°C for 5 hours. After the reaction is completed, the mixture is washed and distilled under reduced pressure to obtain a terminal mercapto perfluoro polymer;
[0062] S2: 2 parts by weight of polycarbonate diol and 0.5 parts by weight of 1,1,3,3-tetramethylguanidine are added to 50 parts by weight of N,N-dimethylacetamide and mixed evenly, CO2 is introduced at 1.3 MPa and 30°C for 60 minutes, 0.7 parts by weight of allyl chloride is added, and the reaction is continued for 40 hours. After the reaction is completed, the mixture is cooled to room temperature, filtered, washed, and dried to obtain a modified polycarbonate;
[0063] S3: 2 parts by weight of terminal mercapto perfluoropolymer, 4 parts by weight of modified polycarbonate, and 0.1 parts by weight of photoinitiator (2,2-dimethoxy-2-phenylacetophenone) are added to 100 parts by weight of dichloromethane, mixed evenly, and irradiated under 300 W ultraviolet light for 60 minutes to obtain fluorine-containing polycarbonate.
[0064] Example 5
[0065] A corrosion-resistant composite material motor housing, which is substantially the same as that of Example 2, except that: the fluorine-containing silicon polycarbonate is replaced by silicon-containing polycarbonate;
[0066] The method for preparing the silicon-containing polycarbonate comprises the following steps:
[0067] S1. Under a nitrogen atmosphere, 3 parts by weight of a silane compound is added to 50 parts by weight of a 50 wt% ethanol aqueous solution and mixed evenly, the pH is adjusted to 5.8, and the mixture is heated to 60° C. for 4 hours. After the reaction is completed, the mixture is centrifuged, washed, and dried to obtain a functionalized polysiloxane; wherein the silane compound is prepared by mixing 3-mercaptopropyltrimethoxysilane, trimethylhydroxysilane, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane in a mass ratio of 2:1:1;
[0068] S2: 2 parts by weight of polycarbonate diol and 0.5 parts by weight of 1,1,3,3-tetramethylguanidine are added to 50 parts by weight of N,N-dimethylacetamide and mixed evenly, CO2 is introduced at 1.3 MPa and 30°C for 60 minutes, 0.7 parts by weight of allyl chloride is added, and the reaction is continued for 40 hours. After the reaction is completed, the mixture is cooled to room temperature, filtered, washed, and dried to obtain a modified polycarbonate;
[0069] S3: 2 parts by weight of functionalized polysiloxane, 4 parts by weight of modified polycarbonate, and 0.1 parts by weight of photoinitiator (2,2-dimethoxy-2-phenylacetophenone) are added to 100 parts by weight of dichloromethane, mixed evenly, and irradiated under 300 W ultraviolet light for 60 minutes to obtain silicon-containing polycarbonate.
[0070] Example 6
[0071] A corrosion-resistant composite material motor housing, which is basically the same as that of Example 2, except that the fluorine-containing silicon polycarbonate is replaced by modified polycarbonate;
[0072] The preparation method of the modified polycarbonate comprises the following steps:
[0073] Add 2 parts by weight of polycarbonate diol and 0.5 parts by weight of 1,1,3,3-tetramethylguanidine to 50 parts by weight of N,N-dimethylacetamide and mix evenly, introduce CO2 at 1.3MPa and 30°C for 60 minutes, add 0.7 parts by weight of allyl chloride, and continue the reaction for 40 hours. After the reaction is completed, cool to room temperature, filter, wash and dry to obtain modified polycarbonate.
[0074] Example 7
[0075] A corrosion-resistant composite material motor housing, which is substantially the same as that of Example 2, except that the fluorine-containing silicon polycarbonate is replaced by a functionalized polysiloxane;
[0076] The method for preparing the functionalized polysiloxane comprises the following steps:
[0077] Under a nitrogen atmosphere, 3 parts by weight of a silane compound is added to 50 parts by weight of a 50wt% ethanol aqueous solution and mixed evenly, the pH is adjusted to 5.8, and the mixture is heated to 60°C for 4 hours. After the reaction is completed, the mixture is centrifuged, washed, and dried to obtain a functionalized polysiloxane; wherein the silane compound is prepared by mixing 3-mercaptopropyltrimethoxysilane, trimethylhydroxysilane, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane in a mass ratio of 2:1:1.
[0078] Example 8
[0079] A corrosion-resistant composite material motor housing, which is substantially the same as that of Example 2, except that the fluorinated silicon polycarbonate is replaced by a terminal mercapto perfluoropolymer;
[0080] The method for preparing the mercapto-terminated perfluoropolymer comprises the following steps:
[0081] 3 parts by weight of perfluorocyclohexyl methyl acrylate are added to 6 parts by weight of dioxane and mixed evenly, heated to 84°C, 0.1 parts by weight of thioglycolic acid and 0.04 parts by weight of dibenzoyl peroxide are added, and the mixture is continued for 6 hours, and the solvent is removed by distillation under reduced pressure to obtain a terminal carboxyl perfluoropolymer; 5 parts by weight of a terminal carboxyl perfluoropolymer and 0.5 parts by weight of pyridine are mixed evenly, and then 3 parts by weight of thionyl chloride are added, and the mixture is heated to 70°C for 4 hours, and then unreacted substances are removed by distillation under pressure, and then 0.4 parts by weight of mercaptoethanol and 0.6 parts by weight of triethylamine are added at 38°C, and the mixture is heated to 62°C for 5 hours. After the reaction is completed, the mixture is washed and distilled under reduced pressure to obtain a terminal mercapto perfluoropolymer.
[0082] Test Example 1
[0083] Corrosion resistance test
[0084] The samples obtained in each example were immersed in 5% hydrochloric acid, 5% sodium hydroxide and 5% sodium chloride solutions for 24 hours, respectively, and the surface conditions were observed.
[0085] Table 1 Test results of corrosion resistance of composite motor housing
[0086]
[0087] As shown in Table 1, the addition of fluorinated silicon polycarbonate and silane coupling agent to the corrosion-resistant composite motor casing to modify the inorganic material improves the dispersibility of the inorganic material in the polycarbonate, enhances the compatibility between molecules, and inhibits the migration of the inorganic material in the polycarbonate composite material, thereby improving its solvent resistance.
[0088] Test Example 2
[0089] Heat and humidity resistance test
[0090] The samples prepared in each embodiment were placed in a constant temperature and humidity aging box at 85°C and 85% RH for 1000 hours. After the aging, the retention rates of tensile strength and impact strength of the materials were tested according to the standard.
[0091] Refer to GB / T1040.1-2018 "Determination of tensile properties of plastics Part 1: General principles" for tensile properties test;
[0092] The simply supported beam notched impact strength performance test was carried out according to GB / T1043.1-2008 "Determination of impact properties of plastics - Part 1: Non-instrumented impact test".
[0093] Table 2 Moisture and heat resistance test results of composite motor housing
[0094] Tensile strength retention rate / % Impact strength retention rate / % Example 1 81.5 80.3 Example 2 96.1 95.9 Example 3 98.4 98.1 Example 4 93.7 93.2 Example 5 88.9 88.5 Example 6 91.8 90.8 Example 7 90.3 90.0
[0095] The present application uses polycarbonate, fluorinated silicon polycarbonate, polybutylene terephthalate, inorganic materials, maleic anhydride grafted ethylene-octene copolymer (MAH-g-POE), antioxidants, and pentaerythritol stearate as raw materials. The raw materials interact with each other and have good mechanical, corrosion resistance, moisture and heat resistance, and flame retardant properties. The preparation method is simple and the cost is low. The corrosion-resistant composite material motor casing prepared by the present application can replace the metal material casing to achieve lightweight and low-cost motor casing.
[0096] As shown in Table 2, the composite material motor housing prepared in Example 3 has good resistance to moisture and heat. Fluorine-containing silicon polycarbonate is added in Example 3, and the fluorine-containing silicon polycarbonate interacts with the polycarbonate, which can effectively retain and maintain the properties of the polycarbonate, and synergistically improve its defects. In this application, mercaptosilane, hydroxysilane, and epoxysilane are used as raw materials to prepare mercapto-containing polysiloxane; fluorine-containing compounds and thioglycolic acid are used as raw materials to prepare terminal carboxyl perfluoropolymers under the action of initiators; at the same time, terminal carboxyl perfluoropolymers and thionyl chloride are used as raw materials to prepare terminal mercapto perfluoropolymers; polycarbonate diol is used as raw material to prepare modified polycarbonate; mercapto-containing polysiloxane, terminal mercapto perfluoropolymer, and modified polycarbonate are used as raw materials, and mercapto-ene click chemistry reaction occurs under the action of ultraviolet light and photoinitiators to obtain fluorine-containing silicon polycarbonate. Fluorine-containing silicon polycarbonate has a three-dimensional network structure and interacts with polycarbonate to improve its resistance to moisture and heat aging, solvent resistance, and its corresponding mechanical properties. The introduction of polysiloxane improves the flame retardant properties of polycarbonate and expands the application field of polycarbonate materials.
[0097] The inorganic material is treated with a silane coupling agent to improve its dispersibility in polycarbonate, enhance the compatibility between molecules, and inhibit the migration of the inorganic material in the polycarbonate composite material, thereby improving its mechanical properties, moisture and heat aging resistance, and solvent resistance.
[0098] Test Example 3
[0099] Flame retardant performance test:
[0100] The flame retardant performance test was carried out according to the vertical combustion test in GB / T2408-2008 "Horizontal and vertical methods for determination of combustion performance of plastics".
[0101] The limiting oxygen index test was carried out in accordance with GB / T2406.2-2009 "Determination of combustion behavior of plastics by oxygen index method Part 2: Room temperature test".
[0102] Table 3 Test results of flame retardant properties of composite motor housing
[0103] UL-94 Limiting oxygen index / % Example 1 V-2 33.6 Example 2 V-1 47.3 Example 3 V-0 49.7 Example 4 V-2 38.5 Example 5 V-1 44.8 Example 6 V-2 35.1 Example 7 V-1 41.4 Example 8 V-2 36.2
[0104] It can be seen from Table 3 that the corrosion-resistant composite motor housing prepared in this application has good flame retardant properties. This application adds fluorinated silicon polycarbonate and silane coupling agent to modify inorganic materials, improves their dispersibility in polycarbonate, enhances the compatibility between molecules, and inhibits the migration of inorganic materials in polycarbonate composite materials, thereby improving their mechanical, moisture and heat aging resistance, and solvent resistance; at the same time, boron nitride nanosheets and carbon nanotubes have flame retardant properties, and the silane coupling agent interacts with the inorganic material and the polysiloxane in the fluorinated silicon polycarbonate. The uniformly dispersed carbon nanotubes and boron nitride nanosheets form a continuous and dense carbon layer during the combustion process, which increases the carbonization rate of the acrylic resin material, avoids the penetration of oxygen and heat into the material, thereby inhibiting the combustion process and improving the flame retardant properties.
[0105] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A corrosion-resistant composite material motor housing, characterized in that: The invention comprises the following raw materials: 60-70 parts by weight of polycarbonate, 10-30 parts by weight of fluorine-containing silicon polycarbonate, 1-6 parts by weight of polybutylene terephthalate, 1-10 parts by weight of inorganic material, 1-10 parts by weight of maleic anhydride grafted ethylene-octene copolymer, 1-5 parts by weight of antioxidant, and 1-5 parts by weight of pentaerythritol stearate; The preparation method of the fluorine-containing silicon polycarbonate comprises the following steps: S1. Under a nitrogen atmosphere, a silane compound is added to a 50-60wt% ethanol aqueous solution and mixed evenly, the pH is adjusted, and the mixture is heated for reaction. After the reaction is completed, the mixture is centrifuged, washed, and dried to obtain a functionalized polysiloxane; S2: adding perfluorocyclohexyl methyl acrylate to dioxane, mixing evenly, heating, adding thioglycolic acid and an initiator, continuing the reaction, and removing the solvent by reduced pressure distillation to obtain a terminal carboxyl perfluoro polymer; mixing the terminal carboxyl perfluoro polymer and pyridine evenly, then adding thionyl chloride, continuing the heating, and then removing the unreacted substances by pressure distillation, and then adding mercaptoethanol and triethylamine at 35-38°C, continuing the heating, washing after the reaction, and distilling under reduced pressure to obtain a terminal mercapto perfluoro polymer; S3: adding polycarbonate diol and 1,1,3,3-tetramethylguanidine to N,N-dimethylacetamide and mixing them evenly, introducing CO2 to continue the reaction, adding a halogen-containing double bond compound, and continuing the reaction. After the reaction is completed, cooling to room temperature, filtering, washing, and drying are performed to obtain a modified polycarbonate; S4: adding functionalized polysiloxane, terminal mercapto perfluoropolymer, modified polycarbonate, and photoinitiator into dichloromethane, mixing them evenly, and irradiating them under ultraviolet light to obtain fluorine-containing silicon polycarbonate; The halogen-containing double bond compound is at least one of 3-chloro-2-methylpropene and allyl chloride.
2. The corrosion-resistant composite material motor housing according to claim 1, characterized in that: The inorganic material is a silane coupling agent modified inorganic material; the silane coupling agent is at least one of 3-isocyanate propyl trimethoxy silane and γ-(2,3-epoxypropoxy) propyl trimethoxy silane.
3. The corrosion-resistant composite material motor housing according to claim 2, characterized in that: The preparation method of the silane coupling agent modified inorganic material comprises the following steps: adding the inorganic material and the silane coupling agent into an ethanol aqueous solution, mixing them evenly, ultrasonically treating them, and then heating them for reaction; after the reaction is completed, centrifuging and collecting the precipitate, washing them, and drying them to obtain the silane coupling agent modified inorganic material.
4. The corrosion-resistant composite material motor housing according to claim 1, characterized in that: The silane compound is a mixture of mercaptosilane, hydroxysilane and epoxysilane.
5. The corrosion-resistant composite material motor housing according to claim 1, characterized in that: The ultraviolet light irradiation condition in step S4 is irradiation under a 300-500W ultraviolet lamp for 10-120 minutes.
6. A method for preparing the corrosion-resistant composite material motor housing according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: uniformly mixing polycarbonate, fluorinated silicon polycarbonate, polybutylene terephthalate, inorganic materials, maleic anhydride grafted ethylene-octene copolymer, antioxidant and pentaerythritol stearate, adding the mixture into a twin-screw extruder, granulating the mixture, adding the mixture into an injection molding machine for injection molding, and obtaining a corrosion-resistant composite material motor housing.